Berteologi Kontekstual Ditengah Jemaat Yang Merindukan Kehadiran Anak Ditengah-Tengah Keluarga Dan Hubungannya Dengan 1Korintus 7 : 40 - Jeicca Melati Siregar; Immanuel Lumbantoruan; Jefri Ade Nasution (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The presence of a child is a blessing in the midst of a Christian family, having children is a very great joy. But there are many brothers and sisters around us who have been building a household for a long time but don't yet have anam, this is a big struggle for them, and has invited a lot of views from various parties. Therefore, the author is interested in using this title to provide contextual theology in the midst of the congregation by completing the 4 stages of Frans Witjen's circle.